Formulation And Evaluation Of Gastroretentive Floating Microspheres And Bilayer Tablets Of Arbekacin And Gatifloxacin For The Treatment Of Urinary Tract Infections - U. Metkari, Nilam; Singh, Himmat; Manjappa, Arehalli S. (Journal of Neonatal Surgery, 2025)
This study aimed to develop and evaluate gastroretentive bilayer tablets and floating microspheres containing Arbekacin and Gatifloxacin for the effective treatment of urinary tract infections (UTIs). Bilayer tablets were formulated with an immediate-release layer of Gatifloxacin and a sustained-release matrix of Arbekacin using HPMC and PEO polymers. Floating microspheres were prepared by emulsification solvent diffusion using polymer blends in varying ratios. Preformulation studies, drug-excipient compatibility (FTIR, DSC), and micromeritic properties were evaluated. In vitro drug release, buoyancy, swelling index, entrapment efficiency, and antimicrobial activity were assessed. Release kinetics were analyzed using Higuchi and Korsmeyer–Peppas models. The optimized bilayer tablets demonstrated rapid Gatifloxacin release (~90% in 45 minutes) and sustained Arbekacin release up to 14 hours. Microspheres provided a 24-hour controlled release profile with high entrapment efficiency (up to 89.4%) and buoyancy (94.6%). Drug release followed non-Fickian kinetics. Antimicrobial testing showed enhanced efficacy against E. coli, K. pneumoniae, and S. aureus. Stability studies confirmed formulation integrity over 90 days. The dual delivery system effectively combines immediate and sustained drug release, improves gastric retention, and demonstrates superior antibacterial activity. It offers a promising strategy for improving treatment outcomes in MDR-UTIs.